Sleep in Antarctica: from the Sleep Disturbances Towards All the Challenges - Shylo , Oleksandr; Lutsenko , Dmytro; Lutsenko , Olena; Babiychuk , Georgiy; Moiseyenko, Yevgen (Problems of Cryobiology and Cryomedicine, 2020)
From the first expeditions, adaptation to the harsh environment of Antarctica, the expeditionists complained of a trouble sleeping. During a long stay on the continent, the polar explorers are exposed to a large number of extreme environmental factors both at the station and outside it, but the main physical factors of sleep disturbances are considered to be the peculiarities of light and photoperiod. Recently, more attention has been paid to clarifying the role of psychological adaptation to the Antarctica conditions, regarding the living in a small group and confined space. Existing methods to prevent the sleep disorders, first of all, comprise the manipulating with light parameters, activity and rest schedules. A thorough preliminary selection of expeditionists to establish the necessary psychological climate, thinking about gender and multicultural characteristics of adaptation can also be considered with the perspective of preventive measures. At the same time, little attention is paid to the investigation of the role of ’non-core’ factors (chronotype, personality traits and features of personal adaptation to the extreme environment of Antarctica), as well as forced contact with cold, affecting sleep. Probl Cryobiol Cryomed 2020; 30(1): 3-23